A new species of Cycloramphus Tschudi (Anura: Cycloramphidae) from the Parque Nacional da Serra dos Órgãos, Southeastern Brazil - Weber, Luiz Norberto; Verdade, Vanessa Kruth; de Oliveira Lula Salles, Rodrigo De; Fouquet, Antoine; de Carvalho-E-Silva, Sergio Potsch (Zootaxa, 2011)
We report here the discovery of a new species of frog associated to the open areas of the highlands of the Parque Nacional da Serra dos Órgãos. The new species, Cycloramphus organensis is characterized by a unique skin texture, medium size (maximum male and female SVL 26.4 mm and 33.3 mm respectively), dorsal surfaces uniformly brick red colored, uniformly areolate skin on dorsum, pupil horizontal, iris with a menisc on upper margin; no fleshy tubercles on eyelid, tympanic annulus concealed beneath skin, macroglands not visible externally, fingers and toes without fringes and webs; supernumerary palmar and plantar tubercles absent, nuptial spines absent. Despite the presence of an iris menisc, a character shared by frogs of both genera Cycloramphus and Zachaenus Cope, the combination of morphological characters is so unique that the allocation of the species to any of these genera remains ambiguous. Consequently, we used additional molecular-based phylogenetic analyses to ascertain the position of the new taxon. The new species proved to be embedded within the genus Cycloramphus.